LA CONSTRUCCIÓN COMO FRONTERA DE LA FORMA: EL LABERINTO DE ANDRÉ BLOC EN CARBONERAS / A construction as a frontier of form: the labyrinth of André Bloc in Carboneras - García-Diego Villarías, Héctor; Villanueva Fernández, María (Proyecto, Progreso, Arquitectura, 2014)
RESUMEN El polifacético arquitecto de origen argelino André Bloc, tras ensayar en varias ocasiones en su jardín de Meudon algunas soluciones plásticas habitables, insertó una de sus esculturas habitáculo en una de las playas almerienses de Carboneras. La construcción, conocida popularmente como ‘El Laberinto’, constituye una obra singular del patrimonio arquitectónico español del siglo pasado y una muestra ejemplar del esfuerzo de integración entre arte y arquitectura. Pero sobre todo, esta insólita vivienda supone un testimonio extraordinario respecto a la frontera que separa arte y arquitectura y restringe una hipotética coalescencia entre ambas: el hecho constructivo marca un límite que, aunque variable, resulta ineludible. SUMMARY After trying some habitable, sculptural solutions in his garden at Meudon, on several occasions, the multifaceted architect of Algerian origin, André Bloc, built one of his habitable sculptures at one of the beaches of Carboneras, in Almeria. The construction, popularly known as “The Labyrinth”, constitutes a unique work from the Spanish architectural heritage of the last century and is a prime example of the force of integration between art and architecture. However, above all, this unusual house represents an extraordinary testimony with respect to the frontier that separates art and architecture and which restricts a hypothetical coalescence between both; the constructive fact defines a boundary which, although variable, is inescapable.